COMMUNITY SERVICES FOR CHILDREN AND YOUTH WITG BEHAVIORAL PROBLEMS AND IN CONFLICT WITH THE LAW: THE IDEA AND REALIZATION OF A DAY CARE CENTER - Gajic, Miona; Hrncic, Jasna; Vucinic Jovanovic, Marija (Serbian political thought, 2023)
The daycare service for children with behavioral problems is one of the services in social care that are based on an ecosystem approach and user participation, and that develop cooperation between all actors and systems in the community and pluralism of services. Ten years ago, there were several active day care centers for children and youth with behavioral problems (in Novi Sad, Kragujevac, Knjazevac, Pozarevac) that had clearly articulated work programs, while according to data for 2022, there are only two licensed ones in the Republic of Serbia provider of this daycare service (in Bor and Kragujevac). A survey was conducted among daycare service providers in both licensed daycare centers. Based on the respondents' answers, we can conclude that the daycare service has multiple positive effects on both users and their families, as well as on the local community. The existence of this type of service contributes to respecting the basic principles of social protection, respecting the recommendations of international instruments and implementing the provisions of domestic legislation. Day care provides opportunities to apply such methods aimed at supporting and empowering young people, gaining insight into the problem, correcting behavior and increasing personal responsibility. A special advantage is the formation of a more intensive relationship between the professional worker and the user as well as his family. Time commitment and a wide range of activities that can be realized in immediate work, but also in the community together with the user, give positive results. The results of the research indicate the importance of children and young people with behavioral problems remaining in the natural environment, that is, their families and communities with the aim of preventing institutionalization. The results of questionnaires and interviews with service providers, on the other hand, point to the need for further improvement of this service in the context of developing mechanisms for the sustainability of its quality and efficiency. Funding, availability and cross–sector networking continue to be a challenge in the implementation and functioning of day care. As one of the results of the research, the importance of adequate training of experts, the need for external supervision and the fight against prejudices that are common in smaller local communities emerges. The lack of this type of service as well as other incidental services of a preventive nature in the community increases the risk of continued antisocial behavior of this group of children and youth, stigmatization and institutionalization.
Keywords: community services; day care centers; children and youth with behavioral problems; conflict with the law